Stabilization of the stator and rotor flux linkage of the induction motor in the asynchronous electric drives with frequency regulation - Vladimir L. Kodkin; Aleksandr Sergeevich Anikin; Aleksander Aleksandrovich Baldenkov (Institute of Advanced Engineering and Science, 2020)
The article is a continuation of the authors' work in research, mainly experimental, asynchronous electric drives with frequency regulation (AED FR) of hoisting-and-transport mechanisms, in which for constructive, operational and other reasons it is difficult to install additional sensors, for example encoders. The results of the analysis of the dynamics of AED FR with two types of sensorless control: vector and scalar are presented in this article. The study was conducted by mathematical modeling in the Simulink application of the MatLab software using standard control system models. The processes of sequential acceleration of the engine to fixed speeds with overload and load shedding on each of them were simulated. At the same time, the speed and effective values of the flux linkages of the rotor and stator and the stator current were monitored, by which the dynamics and efficiency of each type of control were evaluated. As in experimental studies, the dynamic and efficiency of a more stable scalar control was significantly improved by the use of dynamic positive feedback on stator current.